2003
DOI: 10.1042/cs20030073
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal and/or fetal factor V Leiden and G20210A prothrombin mutation with HELLP syndrome and intrauterine growth restriction

Abstract: This study was conducted to investigate the association of maternal and/or fetal factor V Leiden (FVL) and G20210A prothrombin mutation with HELLP syndrome. FVL and G20210A prothrombin mutation were determined using PCR. Sixty-three pregnant women, 36 of them diagnosed with HELLP syndrome, were included in the study. Overall, 68 children were born as a result of these pregnancies and blood sampling was possible in 28 out of 39 children from HELLP patients and 25 out of 29 children from the control women. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 27 publications
1
24
1
2
Order By: Relevance
“…A substantial increase in TXB2 can cause vasoconstriction, platelet aggregation, and thrombosis. If this occurs, thrombosis, fibrinoid necrosis, and atherosclerosis may be seen in the placenta and decidual vessels and can cause spontaneous abortion, preterm delivery, fetal distress, preeclampsia, and fetal growth restriction [10][11][12][13][14]. Studies of fetal growth restriction and preeclampsia performed with blood samples have reported an increase in TXB2 levels [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial increase in TXB2 can cause vasoconstriction, platelet aggregation, and thrombosis. If this occurs, thrombosis, fibrinoid necrosis, and atherosclerosis may be seen in the placenta and decidual vessels and can cause spontaneous abortion, preterm delivery, fetal distress, preeclampsia, and fetal growth restriction [10][11][12][13][14]. Studies of fetal growth restriction and preeclampsia performed with blood samples have reported an increase in TXB2 levels [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Il n'a cependant pas été démontré une corrélation significative entre le HELLP syndrome et la présence d'une thrombophilie qu'elle soit constitutionelle (mutations du facteur V Leiden et de la prothrombine) ou acquise (syndrome des anticorps antiphospholipides) [20][21][22][23][24] [27][28][29]. Toutefois, l'hypertension artérielle (HTA) et la protéinurie peuvent être initialement absentes (10 à 15 % des cas) et le diagnostic doit être évoqué devant des signes digestifs inhabituels au troisième trimestre [4,5,25,30].…”
unclassified
“…Several studies have addressed the role of fetal inherited thrombophilias in pre-eclampsia, only three of them have included a small number of HELLP pregnancies (Table 5) (19,23,28,(33)(34)(35)(36)(37)(38). On the whole, there was no evidence for a strong association.…”
Section: Discussionmentioning
confidence: 72%
“…Previous association studies on thrombophilic genotypes and HELLP syndrome are summarized in Table 4 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Most of them were limited to a small sample size and genotyping was not done simultaneously for all of the three most common inherited thrombophilias.…”
Section: Discussionmentioning
confidence: 99%